Sparrow Preferences for Winter Cover Crops in California's Central Coast - Brennan, Eric B. (Frontiers in Sustainable Food Systems, 2020)
Agriculture in many regions of the world has reduced bird habitat and abundance, and altered avian community structure. A study was conducted on an organic research farm over two winters (Oct to Mar) in an intensive agricultural region of Salinas Valley, CA to determine how cover crop variety and planting density influenced birds. Cover crops were rye (Secale cereale), a mixture of rye and legumes (Vicia spp., Pisum sativum), and a mustard mixture (Brassica juncea, Sinapis alba). White-crowned Sparrows (Zonotrichia leucophyrs), Savannah Sparrows (Passerculus sandwichensis) and Song Sparrows (Melospiza melodia) were observed both years in the study field. Bird droppings in cover crops were quantified and dissected to determine dietary preferences, and sparrow movement when flushed was determined. Dropping number and weight per m2 were at least 10 times greater in mustard than in rye and in the legume-rye mixture. Droppings were dominated by leaf tissue in mustard versus arthropod tissue in rye and legume-rye. Within cover crop variety, plant density did not have a clear or consistent effect on sparrows. Sparrows flushed from cover crops usually settled in mustard. The White-crowned Sparrow fed on mustard leaves and apparently on weed foliage under mustard. The arthropod-dominated droppings in rye and legume-rye cover crops were consistent with the food preferences of Song and Savannah Sparrows. The White-crowned Sparrow’s clear preference for mustard cover crops is likely due in part to their high dietary needs for sulfur-rich amino acids during the prenuptual molt. This paper provides novel information to help farmers and others understand the cover crop preferences of sparrows, and ways that farmers might use mustard cover crops as trap crops to reduce White-crowned Sparrow feeding damage on winter and spring vegetable crops. It also provides evidence of ecosystems services that these sparrows provide by feeding on weed tissue in winter cover crops.